2013
DOI: 10.1007/s12291-013-0343-y
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Effect of dl-Glyceraldehyde and 2-Deoxyglucose in Ehrlich Ascites Carcinoma Bearing Mice and Their Effect on Liver, Kidney and Haematological Parameters

Abstract: Cancer cells generally exhibit increased glycolysis for ATP generation (the Warburg effect). Compounds that inhibit glycolysis have potential applications in cancer treatment. dl-glyceraldehyde (DLG) and 2-Deoxyglucose (2-DG) have been proven effective in the inhibition of glucose metabolism. Ehrlich ascites carcinoma (EAC) cells were injected intraperitoneally (i.p) in 10-12 weeks old Swiss albino mice, weighing between 20 and 30 g. The anticancer activity of DLG and 2-DG were determined by tumor volume, tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Spotty necrosis, venous congestion, sinusoidal congestion, inflammation, and Kupffer cell hyperplasia serve as indicators of hepatic tissue damage [ 58 , 59 ]. In the present and previous studies, similar histopathological findings have also been identified in both EAC mice [ 60 ] and doxorubicin-treated animals [ 61 ]. However, in this study, animals treated with DOX alone did not show any improvement in spotty necrosis but showed reduced venous congestion, sinusoidal congestion, and inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…Spotty necrosis, venous congestion, sinusoidal congestion, inflammation, and Kupffer cell hyperplasia serve as indicators of hepatic tissue damage [ 58 , 59 ]. In the present and previous studies, similar histopathological findings have also been identified in both EAC mice [ 60 ] and doxorubicin-treated animals [ 61 ]. However, in this study, animals treated with DOX alone did not show any improvement in spotty necrosis but showed reduced venous congestion, sinusoidal congestion, and inflammation.…”
Section: Discussionsupporting
confidence: 89%
“…EAC cells were maintained in male BALB/c mice. EAC cells were passaged as per the standard protocols 45 . Briefly 1 ml of sterile PBS was injected in peritoneal cavity of BALB/c mice to dilute the liquid tumor.…”
Section: Methodsmentioning
confidence: 99%
“…Histopathology examination of liver in group 3 (EAC+DOX) indicated sinusoidal blockage and mononuclear cells invasion, however, aggregated/degenerated hepatocytes were lower in the EAC group. There was no corruption, metastatic foci or EAC attack in the liver while in group 4 (EAC+DOX+MMT), there was a mild sinusoidal blockage, moderate vacuolation, and mononuclear cell penetration, yet seriousness was little compared to the EAC group [49]. Mice treated with DOX showed degeneration of hepatocytes with pyknosis and karyolysis of their nuclei.…”
Section: Discussionmentioning
confidence: 93%
“…EAC infused in mice significantly raised serum levels of ALT, AST, and total bilirubin though levels of serum albumin and total protein declined significantly compared to the control mice, suggesting compromised liver function [49]. The total protein levels are decreased in hepatotoxic conditions as consequences of modification in the protein, lipid, carbohydrate or perturbed protein biosynthesis in the cirrhotic liver [50].…”
Section: Discussionmentioning
confidence: 97%